If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
6*x-(7*y) = 1/2 // - 1/2
6*x-(7*y)-(1/2) = 0
6*x-7*y-1/2 = 0
6*x-7*y-1/2 = 0 // + -7*y-1/2
6*x = -(-7*y-1/2) // : 6
x = (-(-7*y-1/2))/6
x = (1/2-(-7*y))/6
x = (1/2-(-7*y))/6
| a-8=12+a | | 3(x-3)/2=6 | | (3^1/2+4)/(6^1/2+2) | | 5-0.015x=0.035x | | 35.60/8 | | -11=z-3 | | 15x-15/7*5x-5/42=18 | | 6x^2=40 | | 28/8 | | -6x+4=6x-116 | | 3x-8x=65 | | 9+4(2p-1)=4 | | -2x+(2x+28)=19 | | 5x-9+3=7x-11 | | -14=6+4x | | 2x+2x-5=7 | | 30=4x+2 | | 11x-49=-2 | | u=6-5/4u | | 12/2a=3 | | 2459u=.1u+.68u | | 3(4)-3y=21 | | Q-12=4 | | Y=2459+-6.8x | | 1.72x-7=0.74 | | x=2459+-6.8Y | | -2=w/-7 | | 32+4X=10.5+3X | | 7v^2-61v-90=0 | | 4/3x+8=x | | k/4=8.2 | | -4x+4(-x+9)=-4 |